Estudo terminológico para análise de domínio de gênero e sexualidade: o caso de termos «fronteiriços» para sistemas de organização do conhecimento - Assis Pinho, Fabio (Estudios LGBTIQ+, Comunicación y Cultura, 2021)
This article is a terminological study to understand the classification of terms considered «borderline» in relation to the gender issue, originating from the domain of homosexuality, where answers were sought on how to link the question of the materiality of the body with the performativity and how to define and classify terms that are «borderline» in relation to gender and how they appear in documentary languages. Material and Methods: An exploratory and documentary research was developed where the investigative corpora were the keywords identified in the scientific articles published in the journals Journal of Homosexuality, in Sexualities and in the Journal of Gay and Lesbian Mental Health, between the years 2011 to 2016 After identification, corpora were classified using Ranganathan's PMEST categories, metafilter and concept maps. Results: 4,356 terms were identified and 35 were considered «borderline» in relation to the issue of gender and sexuality, which demonstrated that there are ways to link the issue of body materiality with gender performance, especially if we observe the concepts of the «borderline» terms, from the classification according to the PMEST categories of Ranganathan, in the metafilter and in the conceptual maps, in order to understand the epistemic aspects of its concepts. Conclusion: It is concluded that the terminological study allows to understand the question of the materiality of the body with the gender performativity, especially if we observe the concepts of the «borderline» terms and the thematic cores presented in the conceptual maps.